Basophil Expansion Protects Against Invasive Pneumococcal Disease in Mice. (26th January 2014) - Bischof, Andrea; Brumshagen, Christina; Ding, Nadine; Kirchhof, Gabriele; Briles, David E.; Gessner, Johannes Engelbert; Welte, Tobias; Mack, Matthias; Maus, Ulrich A.
Abstract : Background. Protein-based vaccination using pneumococcal proteins is a promising approach for efficient vaccines against Streptococcus pneumoniae. Basophils play an important role in enhancing memory immune responses to intact proteins. We examined the impact of increased basophil pool sizes on humoral memory responses to pneumococcal surface protein A (PspA). Methods. Basophil pool sizes in blood, spleen, and bone marrow were increased by either interleukin 3 (IL-3) treatment or by adoptive basophil transfer before secondary PspA immunization. Subsequently, PspA-specific antibody titers and resistance of mice against invasive pneumococcal disease (IPD) was determined. Results. Mice treated with IL-3, which increased basophil pool sizes, and mice receiving a single basophil transfusion responded with significantly higher PspA-specific antibody titers after immunization with PspA. Importantly, however, just a single transfusion of flow-sorted basophils into mice before secondary immunization with PspA significantly protected mice from lethal IPD. Moreover, concomitant blockade of inhibitory FcγRIIB on transfused basophils further substantially increased basophil-mediated protection against IPD in mice. Conclusions. This is the first study to find that a single transfusion of basophils is sufficient to boost protein-based memory responses against pneumococcal protein antigens, thereby providing significant protection against IPD in mice.